2021
DOI: 10.1111/plb.13314
|View full text |Cite
|
Sign up to set email alerts
|

Seed bulb size influences the effects of exogenous brassinolide on yield and quality of Pinellia ternata

Abstract: In recent years, natural Pinellia ternata populations of have gradually been exhausted, while the cultivated yield has been limited due to lack of research and uncertain climate condition. Therefore, it is necessary to explore methods of improving yield and quality in P. ternata using brassinolide (BR) treatments and choice of a suitable seed bulb size.• This article reports the effects of BR and two seed bulb sizes (diameter: 0.5-1.0 cm and 1.0-1.5 cm) on active and nutrient components and antioxidant activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Bulbils are important vegetative propagation organs in P. ternata . Our previous study showed that BR was involved in bulbil formation and development ( Guo et al, 2021a , b ). However, it is not clear about the molecular mechanism of BR regulating bulbil formation and development.…”
Section: Discussionmentioning
confidence: 99%
“…Bulbils are important vegetative propagation organs in P. ternata . Our previous study showed that BR was involved in bulbil formation and development ( Guo et al, 2021a , b ). However, it is not clear about the molecular mechanism of BR regulating bulbil formation and development.…”
Section: Discussionmentioning
confidence: 99%
“…β-sitosterol content was measured based on the previous report with minor modifications [ 53 ]. Dried samples were immersed in an ethyl acetate solution for 12 h. After centrifuging, the supernatant (4 mL) was evaporated in a water bath.…”
Section: Methodsmentioning
confidence: 99%
“…The total alkaloid was assayed according to the report with tiny modifications [ 53 ]. Dried samples (0.2 g) were extracted with ammonium hydroxide (0.5 mL, 25%) and chloroform (5 mL) at 37 °C for one hour.…”
Section: Methodsmentioning
confidence: 99%